JUMPA Vol.4 No.2, Juni 2017 RASIO KEUANGAN DAN REVALUASI ASET TERHADAP PRICE EARNING RATIO: RASIO KEUANGAN DAN REVALUASI ASET TERHADAP PRICE EARNING RATIO - Oky Aji Pamungkas Universitas Pancasila (Sekolah Tinggi Ilmu Ekonomi Y.A.I - Jakarta - Indonesia, 2017)
The purpose of this study was conducted to analyze the effect of divident payout ratio, current ratio, return on equity, debt to equity ratio, total asset turnover and revaluation of asset to price earning ratio in the manufacture company which are recorded in Indonesia Stock Exchange period 2012 - 2014. Problem frame which is proposed is how much influence variable of divident payout ratio, current ratio, return on equity, debt to equity ratio, total asset turnover and revaluation of asset influence to price earning ratio in partially. The sampling technique in this study using purposive sampling resulting in 34 samples of manufacturing firms. The necessary data in this study were obtained from the website idx.go.id, the analysis method used is multiple linear regression.The study concluded that partially Divident Payout Ratio, Return on Equity, Total Asset Turnover and Revaluasi of Asset significant effect on the Price Earning Ratio while Current Ratio and Debt to Equity Ratio no significant effect on Price Earning Ratio.